Primary tracheal Mucosa-associated lymphoid tissue lymphoma treated with a water-jet hybrid knife: a case report - Li, Yishi; Jiang, Jinyue; Herth, Felix; Wan, Tao; Zhang, Rui; Xiao, Meiling; Jin, Xingxing; Xiao, Yang; Guo, Shuliang (Respiration, 2019)
Primary mucosa-associated lymphoid tissue (MALT) lymphoma of the trachea is very rare and is easily misdiagnosed as a bronchogenic carcinoma or benign tracheal tumor. Here, we report a clinical case where a new clinical approach involving a water-jet hybrid knife was employed in the diagnosis and treatment of primary tracheal MALT lymphoma.